A chassis-based kinematic formulation for flexible multi-body vehicle dynamics. Issue 1 (2nd January 2017) - Kang, Jong Su; Lee, Jung Keun; Bae, Daesung
ABSTRACT: This research proposed an efficient implicit integration method for the real-time simulation of flexible multi-body vehicle dynamics models. The equations of motion for the flexible bodies were formulated with respect to the moving chassis-body reference frame instead of the fixed inertial reference frame. The proposed approach does not require evaluation of system Jacobian and its LU-decomposition in time loof of simulation. This is one of the key aspects that enable high computational efficiency of the proposed method. The numerical simulation results of the proposed approach were matched up with those of the conventional approach but the computation time can be reduced by applying the proposed method. The joint constraint and generalized force equations are the same as the equations for rigid vehicle dynamics models because the joints and forces between flexible bodies are connected by the RBE (rigid body element). On the various driving conditions, the numerical simulation results show that the proposed approach yields almost exact solutions compared to the conventional approach. And the proposed approach spends only 22.9% of conventional approach on computation time under CPU 3.2 GHz personal computer.